2013
DOI: 10.1016/j.molcel.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Negative Regulation by the Glucocorticoid Receptor from Genome-wide Profiling of Inflammatory Cistromes

Abstract: Summary How the glucocorticoid receptor (GR) activates some genes while potently repressing others remains an open question. There are three current models for suppression: trans-repression via GR ‘tethering’ to AP-1/NF-κB sites, direct GR association with inhibitory elements (nGREs), and GR recruitment of the corepressor GRIP1. To gain insights into GR suppression, we used genomic analyses and genome-wide profiling of GR, p65, and c-Jun in LPS-stimulated macrophages. We show that GR mediates both activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
280
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(317 citation statements)
references
References 31 publications
33
280
1
3
Order By: Relevance
“…S2), most likely because a repressing complex was assembled on the accessory SUMOylation site located at K294 (K277 in human), therefore leading to the conclusion that GR SUMOylation is instrumental in GC-induced repressing mechanisms involved in tethered repression. Note, however, that it is not excluded that additional factors could be marginally involved in these repressing mechanisms (13,20). Further experiments, performed with GR K310R and GR K310R/K294R double mutant mice to study the effect of GC on a variety of actual inflammatory models, will establish the importance of GR SUMOylation in tethered repression and more generally in GC-induced antiinflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…S2), most likely because a repressing complex was assembled on the accessory SUMOylation site located at K294 (K277 in human), therefore leading to the conclusion that GR SUMOylation is instrumental in GC-induced repressing mechanisms involved in tethered repression. Note, however, that it is not excluded that additional factors could be marginally involved in these repressing mechanisms (13,20). Further experiments, performed with GR K310R and GR K310R/K294R double mutant mice to study the effect of GC on a variety of actual inflammatory models, will establish the importance of GR SUMOylation in tethered repression and more generally in GC-induced antiinflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…TR␤1 has been shown to bind to two half-sites separated by 1-6 base pairs in vitro (21), and several previously identified TREs fit this pattern. Previous ChIP-seq experiments have helped to confirm that the in vitro binding preference of nuclear receptors such as liver X receptor, glucocorticoid receptor and farnesoid X receptor are preserved in vivo (33,36,37). The nuclear receptor LXR is known to bind with high affinity to DR-4 elements (38 -40), whereas PPAR␣ binds to DR-1 elements (41,42), and FXR binds to IR-1 elements (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, genomewide analysis of GR interactions with DNA (i.e. chromatin-immunoprecipitation of GR followed by deep sequencing, or ChIP-seq) indicated that interactions between GR and inflammatory transcription factors do not necessarily lead to repressive regulatory outcomes (11)(12)(13)(14). Moreover, an increasing number of GR-induced genes are now recognized as contributing to inflammatory repression by GCs (15)(16)(17).…”
mentioning
confidence: 99%